2015
DOI: 10.1016/j.jcou.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

CO2–CH4 conversion and syngas formation at atmospheric pressure using a multi-electrode dielectric barrier discharge

Abstract: The conversion of CO2 and CH4 into value-added chemicals is studied in a new geometry of a dielectric barrier discharge (DBD) with multi-electrodes, dedicated to the treatment of high gas flow rates. Gas chromatography is used to define the CO2 and CH4 conversion as well as the yields of the products of decomposition (CO, O2 and H2) and of recombination (C2H4, C2H6 and CH2O). The influence of three parameters is investigated on the conversion: the CO2 and CH4 flow rates, the plasma power and the nature of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 53 publications
2
54
0
Order By: Relevance
“…Because of its advantages over conventional reforming technologies, a lot of research has already been devoted to the plasma‐based conversion of greenhouse gases into value‐added products. Most of the research has been based on pure CO 2 splitting or dry reforming of methane . Pure H 2 O plasmas for the production of hydrogen have also been extensively studied .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its advantages over conventional reforming technologies, a lot of research has already been devoted to the plasma‐based conversion of greenhouse gases into value‐added products. Most of the research has been based on pure CO 2 splitting or dry reforming of methane . Pure H 2 O plasmas for the production of hydrogen have also been extensively studied .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a DBD reactor has a simple design that can easily be up-scaled for industrial applications, as already demonstrated for the ozone synthesis [30][31][32]. We have already demonstrated that our flowing DBD setup presents a good compromise between a reasonable energy efficiency and a high CO2 conversion for low specific energy input (SEI) [33].…”
Section: Note: This Document Is a Pre-print Version You May Use It Amentioning
confidence: 75%
“…6 illustrates the various experimental data for energy efficiency vs. total conversion, obtained from literature, [25][26][27][28]32,33 in comparison with our simulation results, for all conditions investigated. 6 illustrates the various experimental data for energy efficiency vs. total conversion, obtained from literature, [25][26][27][28]32,33 in comparison with our simulation results, for all conditions investigated.…”
Section: Model Predictions In a Wider Parameter Rangementioning
confidence: 94%